Politainment And Public Sentiment Towards Pan And Gerindra Legislative Candidates - Ayalla, Elicia Nabita; Sutjiatmi, Sri; Sugiharto, Unggul (JURNAL TRIAS POLITIKA, 2025)
Political dynamics in the modern era analyze the relationship between politainment (politics as entertainment) and public sentiment towards legislative candidates from the PAN Party and Gerindra Party. This study aims to analyze the influence of politainment on public sentiment through content towards PAN and Gerindra candidates. With the development of social media and the phenomenon of politics being increasingly influenced by entertainment elements, political parties, including PAN and Gerindra, are increasingly utilizing digital platforms to attract public attention. This research uses a content analysis method of various posts on social media Instagram and a survey to measure public sentiment towards legislative candidates from the two parties. This research uses a qualitative method with a phenomenological approach to data analysis using Orange Data Mining software and VosViewer 1.6.20, then data is taken from the comments of Instagram users from several posts on PAN and Gerindra legislative candidates to determine public sentiment. The results provide an overview of how entertainment elements in politics can influence public support and assessment of positive or negative images of legislative candidates, as well as the implications for future political communication strategies. This research contributes to providing deeper insights into how the public responds to and assesses PAN and Gerindra legislative candidates from among artists